Analisa Kepuasan Pelanggan Terhadap Layanan Aplikasi E-Commerce Menggunakan Algoritma C4.5 - Eko Setia Budi; Abdul Rahman Kadafi; Yasdi Kharismawan; Randi Fadillah; Desy Sasqia Putri (STMIK Budi Darma, 2024)
Customer satisfaction is one of the key factors that greatly influences loyalty and business sustainability of an e-commerce application. This research focuses on analyzing the level of customer satisfaction with e-commerce services using the C4.5 algorithm. This research aims to identify key factors that influence customer satisfaction and provide recommendations that can help e-commerce companies improve the quality of their services. Customer satisfaction data is collected through surveys that cover various attributes such as product quality, delivery speed and customer service responsiveness. The analysis results show that the product delivery attribute is the factor that most influences customer satisfaction, with a gain value of 0.337981562. The resulting model has an accuracy of 93%, showing good ability in predicting customer satisfaction. These findings are expected to provide practical insights for e-commerce companies in their efforts to increase customer satisfaction and loyalty.